AQ-2 Reformation in Public Information Announcement Technique of Agricultural Quarantine by Using Digital Applications - Adil Kari Salam Harahap (Hemera Zoa, 2018)
In the implementation of Public Service Information System, an agency needs to provide openly public service information that can be accessed easily, quickly, accurately, and accountably. The information system is a series of activities which include the storaging and managing information and also mechanism of delivering information from organizer to the public which are presented electronically (PermenpanRB No. 13 Tahun 2017).Public information must be conveyed and announced periodicly, soonly, and available in everytime (UU No. 14 Years 2008). With the reformation of this public information announcement technique, it is believed that the objective of UU 14 Years 2008 about Public Information Openness can be achieved. The intended purposes are listed in Article 3:1)    to ensure the right of citizens to know public policy making plans, public policy programs, and public decision-making processes, and the reasons for public decision making;2)    to encourage public participation in the public policy-making process;3)    to enhance the community's active role in public policy making and good Public Agency management;4)    to realize good state administration, which is transparent, effective and efficient, accountable and accountable;5)    to know the reasons for public policy affecting the livelihood of the public;6)    to develop science and intellectual life of the nation; and / or improve the management and information services within the Public Agency to produce quality information services.The First Class of Agricultural Quarantine Station in Tanjung Balai Asahan use social media as a system information. The informations provide in 2 (two) forms, its are photos and videos. Photos and videos are uploaded on Instagram account of the First Class Agricultural Quarantine Station in Tanjung Balai Asahan (@karantina_tbasahan).